Differences in Growth and Development of Infants Aged 6-12 Months Receiving and Not Receiving Exclusive Breastfeeding in Madiun, Indonesia - Lidia Sabattina; Nurlailis Saadah; Rahayu Sumaningsih; Teta Puji Rahayu (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
Exclusive breastfeeding is important for infant growth, development and health. At the Banjarejo Health Center in Madiun City, there was a decrease in the percentage of babies who received exclusive breastfeeding. In 2021 it was 79.99% decreased to 73.6% in 2022. This study aims to analyze the differences in growth and development of infants aged 6-12 months who get and do not get exclusive breastfeeding in the working area of Puskesmas Banjarejo Madiun City. The type of research used an observational analytic method with a cross-sectional approach. The population was all mothers and their babies aged 6-12 months in the working area of Puskesmas Banjarejo Madiun. Sampling using accidental cross-sectional technique with a total sample of 163. Data analysis using Mann Whitney U Test. 91 respondents received exclusive breastfeeding, 73 respondents did not receive exclusive breastfeeding. The results of the study obtained a correlation rate of 0.019, meaning that there is a difference between the growth of infants aged 6-12 months who get and those who do not get exclusive breastfeeding. The correlation number of infant development is 0.010, meaning that there is a difference between the development of infants aged 6-12 months who get and do not get exclusive breastfeeding. In conclusion, there is a difference in the growth and development of infants aged 6-12 months who get and those who do not get exclusive breastfeeding at the Banjarejo Madiun Health Center. Suggestions for the head of the relevant department to hold an ongoing counseling program from prospective brides, during pregnancy, after childbirth regarding exclusive breastfeeding. It is expected that families fully support exclusive breastfeeding.